Laparoscopic versus open colectomy for TNM stage III colon cancer : results of a prospective multicenter study in Italy - Guerrieri, Mario; Campagnacci, Roberto; De Sanctis, Angelo; Lezoche, Giovanni; Massucco, Paolo; Summa, Massimo; Gesuita, Rosaria; Capussotti, Lorenzo; Spinoglio, Giuseppe; Lezoche, Emanuele (Surgery today (Tokyo, Japan), 2012)
Background and Purpose There is still debate about the practicality of performing laparoscopic colectomy instead of open colectomy for patients with curable cancer, although laparoscopic surgery is now being performed even for patients with advanced colon cancer. We compared the long-term results of laparoscopic versus open colectomy for TNM stage III carcinoma of the colon in a large series of patients followed up for at least 3 years. Methods The subjects of this prospective non-randomized multicentric study were 290 consecutive patients, who underwent open surgery (OS group; n = 164) or laparoscopic surgery (LS group; n = 126) between 1994 and 2005, at one of the four surgical centers. The same surgical techniques were used for the laparoscopic and open approaches to right and left colectomy. The distribution of TNM substages (III A, III B, IIIC) as well as the grading of carcinomas (G1, G2, G3) were similar in each arm of the study. The median follow-up periods were 76.9 and 58.0 months after OS and LS, respectively. Results There were 10 (6.1 %) versus 9 (7.1 %) deaths unrelated to cancer, 15 (9.1 %) versus 5 (4 %) cases of local recurrence, 7 (4.2 %) versus 5 (4 %) cases of peritoneal carcinosis, and 37 (22.5 %) versus 14 (11.1 %) cases of metastases in the OS and LS groups, respectively. There was also one case of port-site recurrence after LS (0.8 %). The OS group had a significantly higher probability of local recurrence and metastases ( p < 0.001) with a significant higher probability of cancer-related death ( p = 0.001) than the LS group. Conclusions These findings support that LS is safe and effective for advanced carcinoma of the colon. Although the LS group in this study had a significantly better long-term outcome than the OS group, further investigations are needed to draw a definitive conclusion.